2019
DOI: 10.1101/823393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replacing murine insulin 1 with human insulin protects NOD mice from diabetes

Abstract: 2 16 Abstract 17 Type 1, or autoimmune, diabetes is caused by the T-cell mediated destruction of the insulin-18 producing pancreatic beta cells. Non-obese diabetic (NOD) mice spontaneously develop 19 autoimmune diabetes akin to human type 1 diabetes. For this reason, the NOD mouse has been 20 the preeminent murine model for human type 1 diabetes research for several decades. However, 21 humanized mouse models are highly sought after because they offer both the experimental 22 tractability of a mouse model and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our findings concur with previous work that showed a similar reduction in diabetes incidence in female NOD mice lacking 1 or 2 alleles of Ins1 (10,15), although we did not observe additional protection with the double Ins1 knockout, beyond what was seen with the Cre replacement allele. Similarly, our data are in alignment with a previous study showing replacing the murine Ins1 gene with the human INS gene was found to protect female NOD mice from diabetes in both heterozygous and homozygous states (17). We were unable to detect differences in diabetes incidence in male Ins1 Cre/WT , Ins1 Neo/WT , and Ins1 Neo/Cre NOD mice, perhaps due to an insufficient study period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings concur with previous work that showed a similar reduction in diabetes incidence in female NOD mice lacking 1 or 2 alleles of Ins1 (10,15), although we did not observe additional protection with the double Ins1 knockout, beyond what was seen with the Cre replacement allele. Similarly, our data are in alignment with a previous study showing replacing the murine Ins1 gene with the human INS gene was found to protect female NOD mice from diabetes in both heterozygous and homozygous states (17). We were unable to detect differences in diabetes incidence in male Ins1 Cre/WT , Ins1 Neo/WT , and Ins1 Neo/Cre NOD mice, perhaps due to an insufficient study period.…”
Section: Discussionsupporting
confidence: 91%
“…Insulin is a primary auto-antigen in both murine and human type 1 diabetes pathogenesis (1). Replacing Ins1 with non-antigenic human insulin also protects NOD mice from onset of diabetes (17). Together, these previous observations indicate that insulin 1 gene dosage is a key driver of diabetes in NOD mice.…”
Section: Introductionmentioning
confidence: 99%
“…replaced murine Ins1 with the human insulin gene. This genetic modification almost completely protected NOD mice from developing diabetes, 44 indicating that human insulin, which is more similar to murine insulin 2, is not able to completely replace murine Ins1 as a target of autoimmune responses. Because the expression of human insulin, in this knock‐in model, is driven by the native murine Ins1 promoter, it is unlikely that this phenotype is attributable to changes in expression of inulin in the thymus.…”
Section: T‐cell Responses To Ppi In the Nod Mousementioning
confidence: 98%
“…[41][42][43] Using CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPRassociated protein 9), Elso et al replaced murine Ins1 with the human insulin gene. This genetic modification almost completely protected NOD mice from developing diabetes, 44 indicating that human insulin, which is more similar to murine insulin 2, is not able to completely replace murine Ins1 as a target of autoimmune responses.…”
Section: T-cell Responses To Ppi In the Nod Mousementioning
confidence: 98%
“…While rodent models represent many similarities of human diabetes mellitus, there are limitations for direct clinical use. Considering the insulin gene, humans possess a single copy of the gene on chromosome 11, whereas mice carry two genes, Ins1 and Ins2 [86]. Additionally, mouse models have key variations in physiology, anatomy, and psychology that create challenges for direct comparisons of diabetes mechanisms and treatments in humans [87].…”
Section: Journal Of Diabetes Research and Therapymentioning
confidence: 99%